2021
DOI: 10.1111/odi.13825
|View full text |Cite
|
Sign up to set email alerts
|

A novel lightweight deep convolutional neural network for early detection of oral cancer

Abstract: Objectives To develop a lightweight deep convolutional neural network (CNN) for binary classification of oral lesions into benign and malignant or potentially malignant using standard real‐time clinical images. Methods A small deep CNN, that uses a pretrained EfficientNet‐B0 as a lightweight transfer learning model, was proposed. A data set of 716 clinical images was used to train and test the proposed model. Accuracy, specificity, sensitivity, receiver operating characteristics (ROC) and area under curve (AUC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
88
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(91 citation statements)
references
References 56 publications
1
88
0
2
Order By: Relevance
“…Even the optimal ML models identified during the training stage provided only modest (<80%) levels of specificity ( Table 4 ). It is expected that with a more comprehensive training database and the adoption of more advanced ML models (e.g., deep learning methods) [ 42 , 43 , 44 ], it will be possible to enable automated discrimination of dysplastic and cancerous vs. healthy oral tissue with superior classification performance. Nevertheless, the classification results obtained in the independent maFLIM images used as testing set (ROC-AUC > 0.8, Figure 4 ) strongly support the potentials of an ML-enabled maFLIM-based strategy for automated and unbiased discrimination of dysplastic and cancerous vs. healthy oral tissue.…”
Section: Discussionmentioning
confidence: 99%
“…Even the optimal ML models identified during the training stage provided only modest (<80%) levels of specificity ( Table 4 ). It is expected that with a more comprehensive training database and the adoption of more advanced ML models (e.g., deep learning methods) [ 42 , 43 , 44 ], it will be possible to enable automated discrimination of dysplastic and cancerous vs. healthy oral tissue with superior classification performance. Nevertheless, the classification results obtained in the independent maFLIM images used as testing set (ROC-AUC > 0.8, Figure 4 ) strongly support the potentials of an ML-enabled maFLIM-based strategy for automated and unbiased discrimination of dysplastic and cancerous vs. healthy oral tissue.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the reported accuracy of the deep machine learning techniques in the included studies, it is evident that the deep machine learning technique can play a significant role toward the improved prognostication of oral cancer and guide clinicians in making informed decisions. The approach of using deep learning for prognostication can provide low-cost screening [19,36], smartphone-based solution [17,23], deep learning-based automatic prognostication [18,27,32], and early detection and prediction of outcomes [15,17,23,24,[37][38][39]42].…”
Section: Discussionmentioning
confidence: 99%
“…Related work reported values of 0.8500 and 0.8875 [10], 0.866 and 0.900 [7], 0.89 and 0.97 [14], and 0.867 and 0.845 [15], for sensitivity and specificity, respectively. Whilst we provide a comparative study of models in Table 2, currently, direct comparisons to related work can be difficult to make because their datasets and consequently their methodologies are designed to tackle different challenges.…”
Section: Discussionmentioning
confidence: 99%
“…A study [13] demonstrated that simpler CNN architectures are more suitable when fine-tuning on an oral lesion dataset of limited size, VGG-19 [11] performed the best for the classification of referral vs. non-referral. Shamim [14] used VGG-19 for benign vs. pre-cancerous classification and Jubair [15] used a lightweight CNN for benign vs. suspicious classifications; both restricted to tongue lesions only.…”
Section: Related Workmentioning
confidence: 99%